Perbandingan Implementasi Ct Pro Dan Algoritma C45 Menentukan Pola Penyakit Pasien Stroke (Studi Kasus Rs. Siti Fatimah Palembang) - Abi Yansa; Diana (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The development of adult data mining has penetrated into every segment, this has an effect on the health sector. With these developments can help the process both in health care and disease prevention in patients. Stroke is a disease that is currently the cause of death with a percentage of 10.9% in Indonesia. This happens because of the difficulty in predicting the symptoms experienced. From these problems, technology is needed with the use of data mining to cluster and classify the results of patient medical records in order to overcome the problem of stroke. This study uses a clustering technique by comparing the CT-Pro algorithm and the C45 algorithm. The results of this study indicate that the C45 algorithm produces better accuracy and results than the CT-Pro algorithm.